1999
DOI: 10.1007/s004170050207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Night Vision Spectacles on patients with impaired night vision

Abstract: Patients with impaired night vision can benefit from the NiViS when performing tasks involving contrast and motion perception. Those with normal visual fields and retaining good photopic vision will benefit more than those with constricted visual fields and impaired cone vision. Recommendations regarding desirable improvements of the NiViS and suitability for the individual patient are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 8 publications
3
13
0
1
Order By: Relevance
“…[1214] Control of glare and determination of the proper luminance for activities of daily living, such as reading and driving, is important for the patients’ care. [1516] In the current study, our results showed that adding glare caused a significant decrease of CVA in evening vision. On the other hand, in day vision, the effect of a glare source on CVA was minimal.…”
Section: Discussionsupporting
confidence: 55%
“…[1214] Control of glare and determination of the proper luminance for activities of daily living, such as reading and driving, is important for the patients’ care. [1516] In the current study, our results showed that adding glare caused a significant decrease of CVA in evening vision. On the other hand, in day vision, the effect of a glare source on CVA was minimal.…”
Section: Discussionsupporting
confidence: 55%
“…Our results were thus similar to those in previous studies using binocular night vision goggles that block natural vision [10,11,13,14]. The greatest advantage of our device is that it enables subjects to use their own eyes to recognize objects that they can see, and use the display as a supplement to see the objects they cannot see.…”
Section: Discussionsupporting
confidence: 88%
“…Since the 1970s, several types of devices have been evaluated to address mobility problems due to night blindness [7][8][9][10][11][12][13][14]. Berson et al [7] first reported the helpfulness of a night vision enhancement device based on a military light-intensifier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One small study found that while night-scopes did provide people with RP with improved night vision, the reduced field (about 40 degrees) and cumbersome headsets interfered with head and eye scanning, making the devices useful only for spotting tasks. 138 Other studies have reported on the encouraging development of smaller and easier to use night vision goggles, 165 with some reporting an improvement in walking speeds in real-world night environments. 166,167 Currently, night vision goggles are still an interesting experimental option and should be backed up with a long cane.…”
Section: Night Vision Aidsmentioning
confidence: 99%